A novel approach for classification of loads on plate structures using artificial neural networks - ÜNAL, MUHAMMET (ELSEVIER SCI LTD, 2016)
In this study the location of applied load on an aluminum and a composite plate was identified using two type of neural network classifiers. Surface Response to the Excitation (SuRE) method was used to excite and monitor the elastic guided waves on plates. The characteristic behavior of plates with and without load was obtained. The experiments were conducted using two set of equipment. First, laboratory equipment with a signal generator and a data acquisition card. Then same test was conducted with a low cost Digital Signal Processor (DSP) system. With experimental data, Multi-Layer Perceptron (MLP) and Radial Basis Function (RBF) neural network classifiers were used comparatively to detect the presence and location of load on both plates. The study indicated that the Neural Networks is reliable for data analysis and load diagnostic and using measurements from both laboratory equipment and low cost DSP. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Surface response to excitation method; Load monitoring; Neural networks; Piezoelectric; Digital signal processor